The Role of Intelligent Test Systems in Healthcare Technology - Vamasani, Saahith Guptha (International Journal of Computing and Engineering, 2025)
The intelligent testing system represents a significant development in healthcare technology verification, addressing unique challenges where software failures can directly affect patient safety. This special testing framework involves moral views in healthcare-specific knowledge, regulatory compliance mechanisms, and an integrated verification architecture. The implementation of intelligent test systems fundamentally replaces quality assurance in health technology to align with a moral mandatory patient welfare from the development phase. The domain-quieutenant verification structures imitate authentic clinical scenarios by enabling complicated medical workflows and clinical decision support systems, protecting the information of sensitive patients. Compliance-centered automation tests the regulatory requirements within the architecture, validates functionality, and produces documents for regulator submission. To manage variability in the healthcare environment, a refined approach requires regulated, tested test orchestration and synthetic data generation, which is compatible with the jurisdiction-specific requirements without compromising the verification quality. The moral dimensions of healthcare testing expand the verification beyond technical purity to include prejudice, algorithm transparency, and proper failure-safe implementation. Through the systematic implementation of these advanced testing methods, healthcare technology significantly reduces the implementation time limit in terms of high reliability, better patient results, increased regulatory compliance, and a diverse healthcare environment.